FIELD COMPARISON OF THE PERFORMANCE OF SLATTED AND GENERAL PURPOSE MOLDBOARD - Ahmed. A. A. Hamid; A. A. Alsabbagh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Factorial experiment within randomized complete block design using three replication for field comparison performance slatted and general-purpose moldboard plow. Using least significant design (LSD) 1 % and 5 % was used to compare the mean of treatments. Three factors were used, the first one was depths of tillage 15 and 25 cm, the second was speed of tractor 4.146 and 7.224 km/hr, and the third factor was types of moldboard, slatted and general-purpose moldboard. Slatted moldboard recorded the least slippage of 9.697 %, the fuel consumption of 23.580 L/ha and higher effective field capacity of 0.4239 ha/hr, and field efficiency of 72.543 %. Depth of tillage 15 cm got the least slippage of 6.364 %, fuel consumption of 20.182 L/ha and higher and higher effective field capacity of 0.4402 ha/hr, and field efficiency of 74.187 %. Speed 7.224 km/hr got least fuel consumption 22.939 L/ha and a higher adequate field capacity of 0.5246 ha/hr. Interaction between treatments had a significant effect.